Eksplorasi Tantangan dan Solusi Dalam Pembelajaran Berdiferensiasi Pada Kurikulum Merdeka - Nur Rahmadani Muthaharoh; Riya Kusmita; M. Kurniawan; Selvi Afitri; 4Ali Iskandar Zulkarnain (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Differentiated learning is a concept from the Independent Curriculum, which is expected to be able to overcome student diversity in learning. In its implementation, there are challenges faced by teachers and of course there are solutions to overcome them. This research method is a literature review (library research). The aim of this research is to explore what challenges are faced in differentiated learning and what solutions to overcome them. There are several challenges, namely: various characters that students have, different student learning styles, each student has their own interests, lack of teacher preparation to implement an independent curriculum, teacher abilities, time factors, high pressure, and expensive costs. The solutions are: organizing an even number of students, using appropriate learning strategies, knowing student interests, providing well-designed teacher training, and sufficient operational funds. Keyword: Challenges; Solutions; Differentiated Learning; Independent Curriculum.